2004
DOI: 10.1007/s00234-003-1159-x
|View full text |Cite
|
Sign up to set email alerts
|

Transient detection of early wallerian degeneration on diffusion-weighted MRI after an acute cerebrovascular accident

Abstract: We report three patients with a cerebrovascular accident studied serially by MRI, including diffusion-weighted imaging (DWI). In case 1, DWI 1 day after the onset of left frontoparietal cortical infarcts showed no abnormal signal in the left corticospinal tract. DWI 12 days after onset showed high signal in the corticospinal tract, interpreted as early wallerian degeneration. This had disappeared by 22 days after onset. In case 2, DWI obtained 7 days after the onset of a right internal capsule lacunar infarct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 9 publications
0
33
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] We report postoperative transient reduced diffusion in the ipsilateral striatum and/or thalamus, with diffusion restriction observed on days 7-46 (mostly days 8 -21), and a marked correlation between the surgical location and the distribution of signal abnormalities within the striatum and/or thalamus. This correlation is consistent with the anatomy of neuronal connectivities and suggests that the observed reduced diffusion represents the early phase of secondary neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15] We report postoperative transient reduced diffusion in the ipsilateral striatum and/or thalamus, with diffusion restriction observed on days 7-46 (mostly days 8 -21), and a marked correlation between the surgical location and the distribution of signal abnormalities within the striatum and/or thalamus. This correlation is consistent with the anatomy of neuronal connectivities and suggests that the observed reduced diffusion represents the early phase of secondary neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Diffusion abnormality due to Wallerian degeneration is known to develop within as little as 2 days after injury 12 and to last for at least 2 weeks. 13 Although it has been well-documented that secondary degeneration occurs in the thalamus following ischemic infarction in the MCA territory, [16][17][18] reports on MR imaging findings of secondary degeneration in the striatum have been very sparse. 19 In addition, there have been no reports on the depiction of the early phase of postoperative secondary degeneration by using DWI.…”
mentioning
confidence: 99%
“…22 Additionally, a similar evolution of signal change also was detected in the area of pyramidal tract: a high signal on diffusion-weighted imaging and low apparent diffusion coefficient value were evident in the first 2 weeks after stroke onset and disappeared thereafter. 23,24 More importantly, recent studies reported that diffusion-weighted imaging hyperintensity or apparent diffusion coefficient map hypointensity in the pyramidal tract was correlated with poor motor outcome, suggesting that a diffusion-weighted imaging signal abnormality in the pyramidal tract is an early predictor of motor recovery after cerebral infarction. 9 -11 In 2 longitudinal diffusion tensor imaging studies, a significant increase in mean diffusivity was noted in the ipsilateral thalamus 1 to 6 months after MCA infarction, whereas fractional anisotropy (FA) remained unchanged.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imagingmentioning
confidence: 99%
“…30 These findings suggest that apoptosis may be involved in the secondary thalamic degeneration. In addition, the observation that antiapoptotic Bcl-2 expression was reduced in the thal- Hyperintensity on T2WI at 1 or 2 wk after stroke and becomes less intense 3 mo later 19 No abnormal intensity within 1 mo after stroke Hyperintensity in the dorsomedial and pulvinar nucleus at 6 wk after stroke 2,18 Hypointensity 1-3 mo after stroke Hyperintensity after 3 mo 20,21 DWI Not reported Transient hyperintensity on DWI with decreased ADC within 2 wk after stroke 22 Transient hyperintensity on DWI with decreased ADC within 2 wk after stroke 23,24 …”
Section: Apoptosismentioning
confidence: 99%
“…6 -8 We recently reported and validated a novel method of DCST-DWI signal measurement in acute neonatal stroke. 8 Isolated cases of abnormal DCST-DWI signal have been reported in non-neonatal AIS, 9,10,22 but comparison to those without using a standardized outcome measure has not been described.…”
mentioning
confidence: 99%